2016
DOI: 10.1111/mcn.12321
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and social behavior in preschool children: the mediating effects of neurocognitive functioning

Abstract: Early malnutritional status has been associated with reduced cognitive ability in childhood. However, there are almost no studies on the effect of malnutrition on positive social behavior, and no tests of possible mediating mechanisms. This study tests the hypothesis that poor nutritional status is associated with impaired social functioning in childhood, and that neurocognitive ability mediates this relationship. We assessed 1553 male and female 3-year-olds from a birth cohort on measures of malnutrition, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 100 publications
(141 reference statements)
0
17
1
1
Order By: Relevance
“…First, consistent with previous findings [ 8 , 38 , 39 ], we found that anemic children were more likely to suffer suboptimal cognition development than non-anemic peers. However, unlike previous studies [ 40 , 41 ], our findings did not support associations of anemia with socio-emotional status. The lack of such associations is partly because our findings were obtained after controlling for a wide range of socio-demographic and socioeconomic characteristics, suggesting that these characteristics may have a greater effect on child socio-emotional outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…First, consistent with previous findings [ 8 , 38 , 39 ], we found that anemic children were more likely to suffer suboptimal cognition development than non-anemic peers. However, unlike previous studies [ 40 , 41 ], our findings did not support associations of anemia with socio-emotional status. The lack of such associations is partly because our findings were obtained after controlling for a wide range of socio-demographic and socioeconomic characteristics, suggesting that these characteristics may have a greater effect on child socio-emotional outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Although these studies add to the increasing body of knowledge indicating that poor nutritional status during early childhood and beyond has a negative impact on cognitive development, few have investigated the association between nutritional status and social behaviors and what the potential mediators may be. Liu and Raine () found in a large sample of 3‐year‐old children living in Mauritius that malnourished children had impaired social functioning, which exhibited a dose–response relationship whereby increased malnutrition was associated with more impaired social behavior. Neurocognitive ability was found to mediate the nutrition–social behavior relationship.…”
Section: Nutrition and Child Development Across The Life‐coursementioning
confidence: 99%
“…Although lying outside the framework of 1000 days, the pre-school age (3–5 years) is equally vulnerable to malnutrition and eating problems, which lead to reduced physical, cognitive, and social development [ 5 – 7 ]. Nearly 43% of the children aged 3–5 are underweight in some of the worst-performing districts of India [ 8 ].…”
Section: Introductionmentioning
confidence: 99%